Celebrity in the mirror: the role of celebrity endorseremnt in men’s grooming communication - Abreu, Cleide Azevedo Pinto de (2016)
Presently, more than ever, men’s grooming is seen as a broad category. The problem comes when the previous research about male consumer behavior have neglected some aspects in this subject. The purpose of this dissertation is to examine the role of celebrity endorsement in men’s grooming communication to Generation Y. After identifying some gaps in the literature, with regard to this contemporary subject, the most important variables were defined in order to develop the investigation and draw conclusions, through statistical analysis and validation, about the role celebrity endorsement as source of credibility in men’s grooming communication. According to the design and methodology of this investigation, this research was sustained through in depth marketing analysis (secondary data), and primary data collection via online questionnaire, whereby 168 male respondents, from Brazil and Portugal, were exposed to some advertisement pieces in order to express their opinion and feelings about the subject under investigation. The findings reveal all the relationships among the variables, suggested by the literature, have occurred, presenting a significant relationship in terms of Source Credibility scale dimensions – attractiveness, trustworthiness and expertise. All findings related to this research are properly analyzed in Results chapter. This dissertation aims to contribute to the existing literature with important conclusions about the role of celebrity endorsement and its credibility in men’s grooming advertisement.